The relationship between anthropometric parameters of the foot and kinetic variables during running - Lee, Y. S.; Ryu, J. (Korean Journal of Sport Biomechanics, 2019)
Objective: The aim of this study was to investigate the correlation coefficients between anthropometric parameters of the foot and kinetic variables during running. Method: This study was conducted on 21 healthy young adults (age: 24.8±2.1yes, height: 177.2±5.8cm, body mass: 73.3±7.3kg, foot length: 256.5±12.3mm) with normal foot type and heel strike running. To measure the anthropometric parameters, radiographs were taken on the frontal and sagittal planes, and determined the length and width of each segment and the navicular height. Barefoot running was performed at a preferred velocity (3.0±0.2m/s) and a fixed velocity (4.0 m/s) on treadmill (Bertec, USA) in order to measure the kinetic variables. The vertical impact peak force, the vertical active peak force, the braking peak force, the propulsion peak force, the vertical force at mid-stance (vertical ground reaction when the foot is fully landed in mid-stance or at the point where the weight was uniformly distributed on the foot) and the impact loading rate were calculated. Pearson's correlation coefficient was used to investigate the relationship between anthropometric variables and kinetical variables. The significance level was set to a=.05. Results: At the preferred velocity running, the runner with longer forefoot had lower active force (r=-.448, p=.041) than the runner with short forefoot. At the fixed velocity, as the navicular height increases, the vertical force at full landing moment increases (r= .671, p= .001) and as the rearfoot length increases, the impact loading rate decreases (r=- .469, p= .032). Conclusion: There was a statistically significant difference in the length of fore-foot and rearfoot, and navicular height. Therefore it was conclude that anthropometric properties need to be considered in the foot study. It was expected that the relationship between anthropometric parameters and kinetical variables of foot during running can be used as scientific criteria and data in various fields including performance, injury and equipment development.